Analisis Makna Kewajiban Rehabilitasi Medis Terhadap Pecandu Narkotika (Jurnal Hukum Bisnis Bonum Commune, 2022)
The application of sanctions on narcotics is quite serious, but in fact the perpetrators of crimes are increasing, and for convicts in practice it is inconclusive and prone to recidivism. This can be caused because the criminal conviction by the judge has no impact or is slow on the culprit. So far, judges tend to emphasize more on criminal sanctions, if it is worth the behavior of the perpetrator with the aim that the perpetrator does not repeat his behavior. This can be caused by the existence of a criminal conviction factor by a judge that does not have an impact or deferrent effect on the perpetrators. So far, criminal convictions by judges tend to prioritize criminal sanctions that are worth the perpetrator's actions, with the aim that the perpetrator does not repeat his actions. In general, drug addicts and victims of narcotics crimes have not received access to rehabilitation services, especially drug addicts and victims of narcotics crimes who are in prisons and detention centers. Therefore, the emphasis of the formulation in this study is how to analyze the significance of medical rehabilitation obligations for drug addicts. The methods used in this study are normative methods and approaches to the method of the statutory approach (Statue Approach) and Conceptual Approach (Conceptual Approach) The results of the study found that Makana Medical Rehabilitation Obligations Against Narcotic Addicts are "sick people" who are obliged to undergo treatment by placing them in medical rehabilitation and or social rehabilitation institutions. As a recommendation, the researcher is to the Government and the House of Representatives to add an explanation of narcotics addicts in Article 54 of Law Number 35 of 2009 concerning Narcotics, by including the amount of medical rehabilitation financing provided to drug addicts in Law Number 35 of 2009 concerning Narcotics. Prior to the promulgation of the amount of medical rehabilitation financing, the provision of medical rehabilitation for drug addicts would be easier to implement, and to the community to increase participation in the prevention of narcotics addicts and the accessibility to the settlement of cases in litigation and non-litigation.